PEMBUATAN SEL SURYA TERSENSITASI PEWARNA (SSTP) LAPISAN TiO2/GRAFIT DARI EKSTRAK KELOPAK BUNGA ROSELLA, BERAS KETAN HITAM, DAN UBI JALAR UNGU - nurhidayah nurhidayah; suwarni suwarni; Sri Rahayu Alfitri Usna; Muhammad Ficky Afrianto; faizar farid (Prodi Fisika FST UNJA, 2017)
Fabrication of Dye-Sensitized Solar Cells (DSSC) using working electrodes composed of a mixture of TiO2 and 14% of graphite, which then denoted as TiO2:C14%, has been done. The TiO2:C14% colloid was deposited on a conductive Fluorine Doped Tin Oxide (FTO) glass substrate by using sol-gel-spin coating at the speed of 1500 rpm for 50 seconds. This thin layer was then immersed for 24 hours in different dye solutions extracted from Rosella petals (hibiscus sabdariffa), black glutinous rice (oryza sativa) and purple sweet potato (ipomoea batatas). Composition materials used to fabricate the solar cells were characterized by using x-ray diffraction (XRD) and scanning electron microscope (SEM). The power conversion efficiency (PCE) of the solar cells was measured by using a set of I-V characteristic circuit. The result showed that the highest PCE of 3 x 10-3 % was obtained from the cells based on dye extracted from rosella petals compared to those from black glutinous rice and purple sweet potato. Keywords: DSSC, dye, rosella, TiO2, spin coating, XRD, efficiency.